Foundational hybridity and its reproduction: Security sector reform in Sierra Leone - Peter Alexander Albrecht (Copenhagen Business School (CBS), 2012)
The thesis argues that security sector reform (SSR) has failed according to its own ambition of establishing a `centrally governed state'. A primary reason for this failure is found in the concept of authority that state-building projects and much of the academic work that underpins it. Since the late 1990s, internationally supported efforts to make and consolidate peace in Sierra Leone have been synonymous with SSR. Support was given by the United Kingdom (UK) in particular to contain and ultimately overhaul the armed forces, which staged two coups in 1992 and 1997. Support was also provided to the central government to institute national security coordination and intelligence organizations, and to reestablish the Sierra Leone Police (SLP). The collapsed, but internationally recognized state was to be rebuilt, and security was seen as not only a prerequisite for this process to begin, but its very foundation. The first question of the thesis revolves around why the western universalist state concept came to guide SSR in Sierra Leone, and why it was considered of such fundamental importance to stability internationally. The second question revolves around how to conceptualize authority when actors such as paramount and lesser chiefs that may neither be categorized as state nor non-state are the primary makers of order in rural areas of the country. Speaking of the weakness or failure of a state is a way of describing what it is not, namely a centrally governed set of institutions that is able to make order within the territorial space that defines it. A focus on the state as an analytical concept does not, however, tell us much about how order is then made, and by whom it is made in Sierra Leone. The thesis rethinks what authority is in a way that does not privilege `the state' as an analytical category, a tendency that has dominated much policy and academic thinking. The thesis' empirical basis of doing so is data relating to international policy-making processes, interviews among the key actors of Sierra Leone's SSR process, and ethnographic fieldwork in Peyima, a small diamond mining town in Kamara Chiefdom, Kono District. In a view of authority tied to `the state' lies the conceptualization of a political entity, a bordered power container, which stands above, is detached from, and at the same time encompasses, controls and regulates society. In UK support of Sierra Leone's statebuilding efforts, the practices of traditional leaders and their productive effects in the justice and security field, and enforcing order, were acknowledged. However, failure to respond adequately to their central role in governing Sierra Leone's countryside came in two ways, both of which are related to concepts of the western universalist state that continue to guide SSR. The first failure was embedded in misrecognizing the resilience and productivity of local actors and institutions, and their authority to appropriate, interpret, translate and above all shape the elements of what was offered through SSR. The second failure came in not recognizing the hybrid nature of all actors in the justice and security field, based on the fact that they draw authority to act within the field from numerous sources across physical and symbolic space, in local and national domains. Hybridity is integral to state formation in Sierra Leone. It is foundational, and is historically grounded in the colonial era, articulating an infinite mixture of various forms of authority (from state legislation to status of autochthony and secret society membership). Inevitably, this order was reproduced by SSR, even if the aim of the international actors who supported this process of change had been to eradicate it.
hdl:10398/8549
Keywords: 650